2020
DOI: 10.1111/bph.15284
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine activin C ameliorates chronic neuropathic pain in peripheral nerve injury rodents by modulating the TRPV1 channel

Abstract: The cytokine activin C is mainly expressed in small-diameter dorsal root ganglion (DRG) neurons and suppresses inflammatory pain. However, the effects of activin C in neuropathic pain remain elusive. Experimental Approach: Male rats and wild-type and TRPV1 knockout mice with peripheral nerve injury-sciatic nerve axotomy and spinal nerve ligation in rats; chronic constriction injury (CCI) in miceprovided models of chronic neuropathic pain. Ipsilateral lumbar (L)4-5 DRGs were assayed for activin C expression. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 55 publications
(112 reference statements)
0
23
0
Order By: Relevance
“…The DRG contains neurons, satellite cells, and macrophages. Iba1 is a specific marker for activated macrophages or microglia and is used to label macrophages in the DRG, but not for satellite cells [ 6 , 28 , 29 , 30 , 31 ]. Our immunofluorescence staining studies showed that macrophages in the DRG surround relatively larger neurons, which is similar to previous reports [ 6 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The DRG contains neurons, satellite cells, and macrophages. Iba1 is a specific marker for activated macrophages or microglia and is used to label macrophages in the DRG, but not for satellite cells [ 6 , 28 , 29 , 30 , 31 ]. Our immunofluorescence staining studies showed that macrophages in the DRG surround relatively larger neurons, which is similar to previous reports [ 6 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Iba1 is a specific marker for activated macrophages or microglia and is used to label macrophages in the DRG, but not for satellite cells [ 6 , 28 , 29 , 30 , 31 ]. Our immunofluorescence staining studies showed that macrophages in the DRG surround relatively larger neurons, which is similar to previous reports [ 6 , 30 ]. In Wistar rats, few Iba1-marked cells were found around CGRP-marked neurons, while most Iba1-marked cells were primarily found around NF200-marked neurons at 6 weeks ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations